3D hydrogel/ bioactive glass scaffolds in bone tissue engineering: Status and future opportunities - Aldhaher, Abdullah; Shahabipour, Fahimeh; Shaito, Abdullah; Al-Assaf, Saphwan; Elnour, Ahmed A.M.; Sallam, El Bashier; Teimourtash, Shahin; A. Elfadil, Abdelgadir (Elsevier Ltd, 2023)
Repairing significant bone defects remains a critical challenge, raising the clinical demand to design novel bone biomaterials that incorporate osteogenic and angiogenic properties to support the regeneration of vascularized bone. Bioactive glass scaffolds can stimulate angiogenesis and osteogenesis. In addition, natural or synthetic polymers exhibit structural similarity with extracellular matrix (ECM) components and have superior biocompatibility and biodegradability. Thus, there is a need to prepare composite scaffolds of hydrogels for vascularized bone, which incorporate to improve the mechanical properties and bioactivity of natural polymers. In addition, those composites' 3-dimensional (3D) form offer regenerative benefits such as direct doping of the scaffold with ions. This review presents a comprehensive discussion of composite scaffolds incorporated with BaG, focusing on their effects on osteo-inductivity and angiogenic properties. Moreover, the adaptation of the ion-doped hydrogel composite scaffold into a 3D scaffold for the generation of vascularized bone tissue is exposed. Finally, we highlight the challenges and future of manufacturing such biomaterials.